Construction of run-length waveform sample library in amplitude domain of complex dynamic power signals - YUAN Ruiming; LI Wenwen; WANG Guoxing; LIU Jianping; WANG Xuewei (Diance yu yibiao)
Aiming at the impact of rapid change of complex dynamic power signal on the error of electricity meter, currently published papers only extract a few waveform samples for analysis, which cannot reflect waveform modes of various current variations, and do not further explore characteristics of power signal and its characterization. Therefore, The fundamental amplitude waveforms are extracted for 3 types of typical complex dynamic power signals. Then, characteristic parameters of run-length and their characterization modes are proposed. On basis of analyzing the typical features of amplitude domain, 28 typical run-length waveforms can be extracted by further analyzing multi-run-length characteristics of current amplitude, and then, the sample library of current characteristic waveforms can be established. According to the characteristic of run length, suggestion test points are given for supplementing international and domestic electricity meter standard.